The Multiversity : the deluxe edition - Morrison, Grant (DC Comics, 2015)
"The biggest adventure in DC's history is here! Join visionary writer Grant Morrison, today's most talented artists, and a cast of unforgettable heroes from 52 alternative Earths of the DC Multiverse! Prepare to meet the Vampire League of Earth-43, the Justice Riders of Earth-18, Superdemon, Doc Fate, the super-sons of Superman and Batman, the rampaging Retaliators of Earth-8, the Atomic Knights of Justice, Dino-Cop, Sister Miracle, Lady Quark, and the latest, greatest Super Hero of Earth-Prime: YOU! THE MULTIVERSITY is more than a multipart comic-book series. It's a cosmos spanning, soul-shaking experience that puts YOU on the frontline in the battle for all creation against the demonic destroyers known as the Gentry! Featuring artwork by Ivan Reis (JUSTICE LEAGUE), Frank Quitely (ALL-STAR SUPERMAN), Cameron Stewart (BATGIRL) and many others, THE MULTIVERSITY tells an epic tale that span 52 Earths. Collects THE MULTIVERSITY #1 and 2, THE MULTIVERSITY GUIDEBOOK #1, and these MULTIVERSITY issues: THE SOCIETY OF SUPER-HEROES #1, THE JUST #1, PAX AMERICANA #1, THUNDERWORLD #1, MASTERMEN #1 and ULTRA COMICS #1"--